Determination of benzotriazole in industrial cooling water by fluorescence. Issue 3 (4th May 2017) - Li, Yuanzhen; Wang, Jiajia; Guo, Wenya; Gao, Canzhu; Cheng, Zhongfa
ABSTRACT: Benzotriazole is widely used in various industries to inhibit corrosion. Sensitive instruments and methods are needed to determine this compound in industrial cooling water. Fluorescence spectroscopy was used to determine benzotriazole in this application. The optimum wavelength was evaluated as well as the influence of pH, temperature, and common ions. Ultraviolet-visible absorption spectroscopy showed that there were two peaks: 259 nm and 278 nm. The latter wavelength was shown to be optimum for the determination of benzotriazole. The fluorescence intensity was linear with concentration from 0.4–4 mg/L. The pH, temperature, and presence of other ions had little effect on the analysis. The detection limit was 0.155 mg/L. In summary, fluorescence spectroscopy was demonstrated to be convenient, sensitive, and economical for the determination of benzotriazole in industrial cooling water.